Competitividade dos municípios turísticos do estado de São Paulo através da aplicação de um modelo de índice de competitividade - Oliani, Laerte Gil Nicaretta (2022)
The tourism activity presents a growing relevance and stands out for its economic importance, placing itself among the main items that generate foreign exchange and contributing significantly to the GDP, regional development and the creation of jobs directly and indirectly. Tourism, in its essence, is a multidimensional and multifaceted activity, which brings about contact with many different lives and economic activities, and can be "thought of" as a wide range of individuals, businesses, organizations and places that combine in some way to provide a travel experience (COOPER et al., 2001). Consequently, investigating competitiveness and its attractiveness factors – such as environment, public policies, infrastructure, natural resources and cultural resources – becomes an important tool for marketing actions in the aid of competitive and cooperative strategies in the management of tourist destinations, influencing their economic development. In view of this, the objective of this work, therefore, was to verify the tourist attractiveness factors and their degree of influence on the competitiveness of tourist municipalities through the elaboration of a competitiveness model, through which the characteristics of attractiveness and public management were examined, as well as their regional development. Regarding the methodology employed to make this research feasible, an exploratory study was carried out comprising the application of a structured script, with closed questions, sent to the public managers of 48 Municipalities of Tourist Interest (MIT) of the State of São Paulo. Moreover, seeking to validate the results found in the empirical application of the questionnaire, these were submitted to statistical reliability tests. In relation to the objective proposed in this work, the results presented show that the “Cultural attractions”, “Natural attractions”, “Public policies”, and “Marketing” pillars have the greatest influence on attractiveness. Complementing this, in relation to the level of competitiveness of the municipalities, the research shows that more than 50% have medium and low levels, suggesting the need for the implementation of actions by municipal managers